Computational fluid dynamics-multibody system dynamics bidirectional coupling calculation and flow-induced vibration evaluation of a high-speed pantograph-catenary system - Zhuojun Li; ChunJiang Chen; Huapu Song; Gang Yang; Jun Yang; Huadong Yao; Jiqiang Niu (Engineering Applications of Computational Fluid Mechanics)
Increasing the speed of a pantograph deteriorates its aerodynamic performance and aggravates the problem of flow-induced vibration, which is not conducive to the stability of the pantograph – catenary system (PCS). Currently, commercial high-speed trains operate at speeds exceeding 350 km/h, with line test speeds exceeding 450 km/h, making the impact of airflow on pantograph dynamics increasingly significant. Therefore, a simulation study on the bidirectional coupling between pantograph aerodynamics and structural dynamics is urgently needed. This study proposes a bidirectional coupling method for the pantograph based on overset grids. The user-defined functions (UDF) in Fluent enable real-time data exchange between aerodynamic forces and structural displacements. The flow field was modelled using the Shear Stress Transport k–ω turbulence model and Reynolds-averaged Navier – Stokes equations, and the dynamics is computed by Newmark-Beta solving the differential equations. It was found that the calculation method in this study was reliable and efficient. The motion of the pantograph assembly in the flow field will change the airflow mode, thus affecting the aerodynamic characteristics of the assembly, and the high-frequency and stochastic aerodynamic excitation will lead to an increase in vibration of the pantograph assembly, especially at the contact strip. For example, when the pantograph operated in the knuckle-upstream direction at 450 km/h, it exhibited poor PCS interaction, with a mean contact force of 50 N, a standard deviation of 36 N, and an overall offline rate of 7%. This study introduced a novel approach to pantograph fluid – structure coupling, offering valuable insights for predicting high-speed pantograph performance and evaluating PCS interactions.